Infective Endocarditis Caused by Pseudomonas stutzeri: A Case Report and Literature Review - Marwan J. Alwazzeh; Feras A. Alkuwaiti; Moammer Alqasim; Sarah Alwarthan; Yasser El-ghoneimy (Infectious Disease Reports, 2020)
Pseudomonas bacteria are widespread pathogens that account for considerable infections with significant morbidity and mortality, especially in hospitalized patients. The Pseudomonas genus contains a large number of species; however, the majority of infections are caused by Pseudomonas aeruginosa, infections by other Pseudomonas species are less reported. Pseudomonas stutzeri is a ubiquitous Gram-negative bacterium that has been reported as a causative agent of some infections, particularly in immunocompromised patients but has rarely been reported as a cause of infective endocarditis. Here, we report a case of a 55-year-old female with no significant medical history who presented with exertional dyspnea, productive cough, and fever. She was diagnosed as a case of acute anterior ST myocardial infarction, underwent double valve replacement surgery, and was found to have infective endocarditis caused by Pseudomonas stutzeri.